Expression and Clinical Significance of Sperm-Associated Antigen 9 in Patients With Endometrial Carcinoma. Issue 1 (1st January 2012) - Yu, Peng; Yan, Lei; Zhang, Hui; Lin, Xiaoyan; Zhao, Xingbo
Abstract : Objective: To investigate the expression and humoral immune response of sperm-associated antigen 9 (SPAG9) in endometri al carcinoma. Methods: Sperm-associated antigen 9 gene expression levels were evaluated in endometrial carcinoma, endometrial hyperplasia, adjacent tissues, and normal endometrial tissues by reverse transcriptase-polymerase chain reaction, immunohistochemistry, and Western blot. Sperm-associated antigen 9 concentration in serum samples from 10 healthy women, 20 women with benign diseases, and 50 women with endometrial carcinoma was detected by enzyme-linked immunosorbent assay. Results: (1) Sperm-associated antigen 9 antibodies were detected in approximately 72% of patients with endometrial cancer but not in healthy controls. (2) A significant difference has been found among pathological types and degrees ( P < 0.05), and it was also found to be expressed in transferred lymph nodes. (3) Sperm-associated antigen 9 serum concentration (ng/mL) of patients with endometrial carcinoma is significantly higher than those of the healthy group ( P < 0.05). Patients harboring grade 3 endometrial carcinoma were found to have significantly higher SPAG9 concentrations than those of grade 1/grade 2 ( P = 0.003). Conclusions: SPAG9 is positively expressed in endometrial cancer, and with a high humoral immune response in patients. It may serve as a new type of endometrial cancer markers for early detection, diagnosis and treatment.